Monitoring revenue trends and tax reforms in Member States 2008 - Joint EC-EPC 2008 report (Luxembourg, 2009)
"Based on the mandate of the ECOFIN Council, the work program of the Working Group on the Quality of Public Finances (EPC-QPFWG attached to the Economic Policy Committee (EPC)) has identified the efficiency of tax systems as a key issue for further work. The EPC-QPFWG has decided that this work should, among others, take the form of an annual report.